2007
DOI: 10.1176/ajp.2007.164.5.813
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive Endophenotypes in a Multiplex Multigenerational Family Study of Schizophrenia

Abstract: In a multigenerational multiplex design, the authors demonstrated that neurocognitive measures are associated with schizophrenia, differentiate unaffected relatives from comparison subjects, and may have significant presumed heritability. Therefore, they are endophenotypes suitable for genetic studies. Accuracy and speed can be differentially sensitive to presumed genetic liability.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
145
6
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 201 publications
(169 citation statements)
references
References 41 publications
16
145
6
2
Order By: Relevance
“…All published studies used different face recognition tasks, differences in the results might therefore also stem from the different tasks. Our findings within the group of schizophrenia patients fit to the well-established facial memory disturbance in schizophrenia in general [3,4,8,47] . However, the finding is in contrast to the results of Lykouras et al [26] who reported no differences between patients with and without DMS in the performance in a variety of neuropsychological tasks, including the Benton visual retention task.…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…All published studies used different face recognition tasks, differences in the results might therefore also stem from the different tasks. Our findings within the group of schizophrenia patients fit to the well-established facial memory disturbance in schizophrenia in general [3,4,8,47] . However, the finding is in contrast to the results of Lykouras et al [26] who reported no differences between patients with and without DMS in the performance in a variety of neuropsychological tasks, including the Benton visual retention task.…”
Section: Discussionsupporting
confidence: 87%
“…Several studies have focused on face identity and face emotion recognition in schizophrenia. Poor accuracy in face identity recognition has been reported in comparison to healthy controls [3][4][5] as well as to psychiatric controls [1,6] . The impairment is more pronounced in patients with a longer duration of illness [7] , suggesting progression over the course of the disease.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…39,41,45,46 The fact that TD transcends formal diagnostic categories is consistent with the nonspecificity of many symptoms of SMI and with the nonspecificity of many cognitive and biological phenotypes in probands and in their clinically unaffected relatives. 6,[47][48][49][50][51][52][53][54][55][56][57][58][59][60] This nonspecificity is also consistent with the substantial (but incomplete 61,62 ) overlap in genetic susceptibility loci across psychiatric disorders [63][64][65][66][67][68][69][70] and with recent work documenting that the familial aggregation of psychiatric disorders is much less specific than had been thought. [71][72][73][74][75][76][77] Both Kraepelin and Bleuler observed that the biological family members of SZ patients often displayed what appeared to be attenuated SZ traits (eg, odd speech), and concluded that the psychopathology of SZ was not limited to the psychotic form of the illness.…”
Section: Introductionsupporting
confidence: 68%
“…IQ), executive functions, sustained attention/ vigilance and verbal declarative memory [22][23][24][25]. In addition to their potential roles in furthering an understanding of the genetic etiology of schizophrenia, neuropsychological endophenotypes are significant for clinical/functional reasons.…”
mentioning
confidence: 99%